2014
DOI: 10.1111/jgh.12482
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of a novel disposable sheathed gastroscopic system in clinical practice

Abstract: Compared with the conventional gastroscope, the novel disposable sheathed gastroendoscope is safe and more efficient in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 13 publications
0
24
0
Order By: Relevance
“…Four teams of researchers (A, D, F, H) took samples for microbial cultures to evaluate the sheaths’ ability to prevent contamination of reusable endoscope components . These studies found no growth or low levels of growth in both sheathed and unsheathed endoscopes, with similar findings in each group (Table ).…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…Four teams of researchers (A, D, F, H) took samples for microbial cultures to evaluate the sheaths’ ability to prevent contamination of reusable endoscope components . These studies found no growth or low levels of growth in both sheathed and unsheathed endoscopes, with similar findings in each group (Table ).…”
Section: Resultsmentioning
confidence: 93%
“…In seven studies (A, F, H, I, K, L, R), researchers evaluated sheath durability. No breaches were detected in any sheaths . The authors of one study (I) noted that friction caused the sheath to cling to the cystoscope in 4 of 27 procedures, making its removal from the cystoscope difficult …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The development of a portable disposable ultrathin endoscope (DUE) would increase patient satisfaction, prevent unnecessary sedation, and reduce infection. [35] …”
Section: Introductionmentioning
confidence: 99%